Leucas mollissima, a source of bioactive compounds with antimalarial and antimycobacterium activities - Chinchansure, Ashish A.; Arkile, Manisha A.; Shukla, Anurag; Shanmugam, Dhanasekaran; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letter, 2015)
A phytochemical investigation of the acetone extract from the aerial parts of Leucas mollissima afforded one new (−)epi-marmelo lactone, (2 S, 4R, 6 S)-2,6-dimethyl-6 hydroxy-7-ene-4-olide (1), along with five known compounds, schensianol A (2), vanillin (3), β-hydroxy propiovanillone (4), lanost-9(11),25-diene-3β,24β-diol (5), and lanost-9(11),23E(24)-diene-3β,25-diol (6). Similarly, an investigation of the methanol extract of the aerial parts of L. mollissima resulted in the isolation of three known compounds, (+)-syringaresinol (7), anisofolin A (8), and apigenin 7-O-β-D(− 6′′-p-E-coumaroyl)-glucoside (9). Structure elucidation of the isolated compounds was carried out using detailed analysis of 1D and 2D nuclear magnetic resonance. All compounds were evaluated for antimalarial activity against Plasmodium falciparum (3D7) and for antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Compound 8 was found to have promising antimalarial activity (IC50 4.39 ± 0.25 µM), promising antimycobacterium activity [IC50 4.50 ± 0.75 µM (3.31 µg/mL)] against M. tuberculosis H37Ra and at 100 µg/mL, showed 55.6 % inhibition of M. bovis. Compound 9 showed moderate inhibition of P. falciparum growth (35 % inhibition at 10 µM) with respect to the positive control atovaquone and 67.4 % inhibition against M. bovis at 100 µg/mL with respect to the positive control rifampicin.